HISTORICAL AND DIDACTIC THEMES IN BUSTAN AL-SALATIN BY NUR AL-DIN AL-RANIRI: A STUDY BASED ON BOOK I-BOOK IV - Hamzah, Norhayati Hj; Aziz, Jamaluddin (Journal of Al-Tamaddun, 2019)
Bustan al-Salatin fi Dhikr al-Awwalin wa al-Akhirin (The Garden of the Kings on the Recollection of the Past and Present) (henceforth Bustan) is a work of Islamic history written by Nur al-Din al-Raniri (cited hereafter al-Raniri) in the seventeenth century Aceh. It consists of seven books with the total of 60 chapters. The structure of Bustan was divided into two; history and didactic. The historical part began with the creation of the universe until the history of the Prophets and Rulers. Meanwhile, the didactic element contained stories of the caliphs in Islamic history and the pious saints of Allah. Both structures were the manisfestation of al-Raniri’s concept of Islamic history that is based on the concept of tawhid in Islam. Al-Raniri’s concept of Islamic history leads to the emergence of several historical themes in Bustan which was largely influenced by the historical themes in the Qur’an. Therefore, this article endeavours to analyze the historical themes in Book I-Book IV of Bustan. It employed a qualitative research approach that applies the technique of documentation in collecting data while inductive approach to content analysis was utilized for data analysis. The main document used was the manuscript of Bustan al-Salatin (Raffles Malay 8). The finding reveals that there are many historical themes in Bustan such as the creation of the universe, history of the Prophets in Islam and didactic theme.